Medication errors in a parturient: A huge cost to two lives - Manpreet Kaur; Bharat Yalla; Anjan Trikha (Wolters Kluwer Medknow Publications, 2022)
Medication errors in a parturient can be devastating as two lives are involved. Owing to the absence of critical incident reporting in parurients in multiple countries of the world, these errors are underreported. We herein discuss the common medication errors in a parturient, the published literature, and the management protocols practiced.